Genome sequencing for detection of pathogenic deep intronic variation: A clinical case report illustrating opportunities and challenges. Issue 10 (22nd June 2021) - Walker, Susan; Lamoureux, Sylvia; Khan, Tayyaba; Joynt, Alyssa C. M.; Bradley, Melissa; Branson, Helen M.; Carter, Melissa T.; Hayeems, Robin Z.; Jagiello, Lukasz; Marshall, Christian R.; Meyn, M. Stephen; Miller, Steven P.; et al.
Abstract: Variants in JAM3 have been reported in four families manifesting a severe autosomal recessive disorder characterized by hemorrhagic destruction of the brain, subependymal calcification, and cataracts. We describe a 7‐year‐old male with a similar presentation found by research‐based quad genome sequencing to have two novel splicing variants in trans in JAM3, including one deep intronic variant (NM_032801.4: c.256+1260G>C) not detectable by standard exome sequencing. Targeted sequencing of RNA isolated from transformed lymphoblastoid cell lines confirmed that each of the two variants has a deleterious effect on JAM3 mRNA splicing. The role for genome sequencing as a clinical diagnostic test extends to those patients with phenotypes strongly suggestive of a specific Mendelian disorder, especially when the causal genetic variant(s) are not found by a more targeted approach. Barriers to diagnosis via identification of pathogenic deep intronic variation include lack of laboratory consensus regarding in silico splicing prediction tools and limited access to clinically validated confirmatory RNA experiments.